Hubungan Pemberian Poster Terhadap Motivasi Pencegahan Anemia Pada Ibu Hamil Di Wilayah Kerja Puskesmas Baki Sukoharjo - Ayu, Yennyka Dwi; , Sulastri, SKp.,M.Kes (2017)
Anaemia in pregnant women to be a problem in the world, because of anemia in pregnant women is closely associated with mortality and morbidity in the mother and baby, including miscarriage, stillbirth, rematuritas, low birth weight. Attempts to overcome these problems need to be given support to pregnant women in a way given the poster in order to reduce the occurrence of anemia in pregnancy. The existence of the poster is very interesting because it combines elements of short words and images in one place, making it possible for the reader to be easily read. This study aimed to analyze the relationship giving motivational poster on the prevention of anemia in pregnant women in Puskesmas Baki, Sukoharjo. This research is a form of pre-experimental with one group pre test and post test design. The study population was all pregnant women first and second trimester anemia in Puskesmas Baki, Sukoharjo totaled 58 pregnant women out of 424 pregnant women who went to the Health Center Baki, Sukoharjo. The research sample group of 58 pregnant women were taken by purposive sampling technique. The collection of research data using a questionnaire and analyzed using paired samples t-test. The results showed test results paired sample t-test motivation before and after values obtained poster thitung 16.465 (p-value) 0,000 so H0 is rejected. Conclusion The study demonstrated an association giving motivational poster on the prevention of anemia in pregnant women in Puskesmas Baki, Sukoharjo.